Aesthetic subunit reconstruction of basal cell carcinoma face - Garg, Paheli; Jain, R. K.; Vashistha, Aakansha; Khushalani, Asha (International Surgery Journal, 2023)
Background: Arising from the basal cell layer of epidermis; BCC is one of the most common cutaneous malignancy encountered in elderly (77%) followed by SCC (20%) and malignant melanoma (3%). Method: A prospective observational study was conducted at department of plastic and reconstructive surgery with 50 patients included for over a span of 2 years. Patients with biopsy confirmed BCC lesion over face were included and were grouped on the basis of subunit involved and type of flap done. Results: The 50 patients were included which comprised of 16(32%) males and 34 (68%) females. Mean age was 61±10.2 years. Smallest defect size was of 1.5 cm2 whereas largest defect size was of 5 cm2. Cheek was the most common site of occurrence. Cheek advancement flap was the most commonly performed flap. Conclusions: Reconstruction of facial subunit post BCC excision with local tissue has superior aesthetic outcome in terms of colour and texture than any other modality.